#TITLE_ALTERNATIVE# - SUKARIAWAN (NIM 13002054), KETUT
The estimation of parameters involved in chemical processes play an important role because it is useful to determine the appropriateness between the model developed with actual behavior of the process so that the model and parameter that result in optimum process conditions can be determined. The appropriate or most realistic parameter is obtained through a fitting or optimisation method. This research aims at studying the parameter estimation method that has high accuracy and precision, which is the simulated annealing combined with the simplex method. The characteristic comparison between the simulated annealing and the simplex methods is done by reviewing three case studies that are the permeability of gas through a membrane, the kinetics of lactic acid fermentation, and the disturbance profile on a dual tank system. The simulated annealing method produces a high level of accuracy and dependability but has a low level of precision and necessitates a large amount of iterations. The simplex method produces a high level of precision but with low accuracy and dependability and the resulting parameter may not fall within a reasonable range of values.